2015
DOI: 10.3390/ijms161226146
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Intracranial Pressure Monitoring and Its Significance in Managing Traumatic Brain Injury

Abstract: Intracranial pressure (ICP) measurements are essential in evaluation and treatment of neurological disorders such as subarachnoid and intracerebral hemorrhage, ischemic stroke, hydrocephalus, meningitis/encephalitis, and traumatic brain injury (TBI). The techniques of ICP monitoring have evolved from invasive to non-invasive—with both limitations and advantages. Some limitations of the invasive methods include short-term monitoring, risk of infection, restricted mobility of the subject, etc. The invasiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 127 publications
1
92
0
1
Order By: Relevance
“…In summary the possible effects adeversos stand out as isquemia cerebral, 6,13 hypoxia/hypoxemia cerebral, [14][15][16][17][18][19][20][21][22] The main secondary causes (extracranial) are airway obstruction; Hypoxia or hypercapnia or hypercarbia (hypoventilation); Hypertension (pain / cough) and hypotension (hypovolemia / sedation); Posture of the patient (head rotation); hyperpyrexia; seizures; And metabolic drugs (e.g., tetracycline, rofecoxib, divalproex sodium, lead poisoning); Others (eg, cerebral edema high altitude, liver failure). The causes of HIC postoperative can present as a mass lesion (hematoma); Edema; Increased cerebral blood volume (vasodilation); LCR disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary the possible effects adeversos stand out as isquemia cerebral, 6,13 hypoxia/hypoxemia cerebral, [14][15][16][17][18][19][20][21][22] The main secondary causes (extracranial) are airway obstruction; Hypoxia or hypercapnia or hypercarbia (hypoventilation); Hypertension (pain / cough) and hypotension (hypovolemia / sedation); Posture of the patient (head rotation); hyperpyrexia; seizures; And metabolic drugs (e.g., tetracycline, rofecoxib, divalproex sodium, lead poisoning); Others (eg, cerebral edema high altitude, liver failure). The causes of HIC postoperative can present as a mass lesion (hematoma); Edema; Increased cerebral blood volume (vasodilation); LCR disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The causes of HIC postoperative can present as a mass lesion (hematoma); Edema; Increased cerebral blood volume (vasodilation); LCR disorders. 5,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The most commonly used technique in clinical practice to monitor the peak involves an intraventricular or intraparenchymal catheter system, which is still considered the gold standard for monitoring ICP. These advances in PIC monitoring technique provides a variety of methods to assess ICP.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the work of Chestnut, who conducted a prospective study in which he reported that the use of ICP is no better than using image studies and clinical examination in the intensive care management of traumatic brain injury, these results cannot be extrapolated in all the cases. (9)(10)(11)(12)(13)(14)(15). The BTF recommends the use of ICP monitoring for the management of patients with neuronal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of noninvasive monitoring of ICP is attractive, as it eliminates most of the problems associated with invasive monitoring. 1 Thus, a new ICP monitoring method has been discovered and developed in Brazil that is minimally invasive. An extensometer with a strain gauge sensor is attached to the skull and is capable of capturing the bone deformations resulting from the variation of intracranial pressure.…”
Section: Introductionmentioning
confidence: 99%